Relationship of safety culture on ergonomics practices at Kemaman supply base / Roziela Mustapa - Mustapa, Roziela (2016)
The purpose of this study is to identify the safety culture among the operators and it relationships on ergonomics practices in the organization. In order to determine the culture of safety the effect of it, three factors that have been determined which are commitment and leadership, motivation and safety management practices. A survey was carried out with 70 respondents. The relationship of commitment and leadership, motivation and safety management practices were interpreted by using Pearson correlation significant. The results showed there are positive relationship between the dependent variable and independent variables. The highest factor contributed to the ergonomics practices is safety management system with the significance level 0.000, the next factors is motivation with significance level 0.001 and the last factor commitment and leadership with significance level 0.077. Method that has been used to collecting the data for this research are by distributed a set of questionnaires which consists of 14 questions. The questionnaires were distributed randomly to the operators at Pangkalan Bekalan Kemaman department. Likert scale was used to measure all variable in order to see the respondent’s agreement and disagreement on the statement given. Reliability test, descriptive analysis and correlation analysis were the data analysis techniques that have been used by the researcher